The Effect of Buerger Allen Exercise on Muscle Cramps in Preventing Intradialysis Emergency - Sulistyaningrum, Danny Putri; Septianingtyas, Maya Cobalt Angio; Sutejo, Mianti Nurrizky (Babali Publisher, 2024)
Introduction: Hemodialysis is a kidney replacement therapy for patients with stage V chronic kidney disease. During hemodialysis, patients often complain of muscle cramps. More than ¾ of hemodialysis patients have experienced muscle cramps. This condition causes discomfort and anxiety, which can reduce their quality of life. If the patient shortens the duration of hemodialysis, the process of removing toxins and excess fluid will not be optimal. This study aimed to investigate the effect of Buerger Allen exercises on muscle cramps in intradialysis patients. Methods: This study used a quasi-experimental design with a two-group pretest-posttest control group structure. The sample consisted of 64 hemodialysis patients at Klinik Ginjal dan Hipertensi Lestari, selected using a consecutive sampling technique. The sample was divided into two groups: 32 in the treatment group and 32 in the control group. The inclusion criteria were ages 25 to 70, compos mentis, able to read and write, willing to participate, and undergoing routine hemodialysis twice a week for at least 4 hours. Statistical analysis was performed using the Mann-Whitney test. Results: The results showed that the mean rank in the treatment group was higher than in the control group (44.97 vs. 20.03). Statistical analysis showed a p-value of 0.000 (<0.05). Conclusion: Buerger Allen exercises have a significant effect on reducing muscle cramps in intradialysis patients.